The Large Second‐Harmonic Generation of LiCs2PO4 is caused by the Metal‐Cation‐Centered Groups. Issue 15 (8th March 2018) - Cheng, Xiyue; Whangbo, Myung‐Hwan; Guo, Guo‐Cong; Hong, Maochun; Deng, Shuiquan
Abstract: We evaluated the individual atom contributions to the second harmonic generation (SHG) coefficients of LiCs2 PO4 (LCPO) by introducing the partial response functionals on the basis of first principles calculations. The SHG response of LCPO is dominated by the metal‐cation‐centered groups CsO6 and LiO4, not by the nonmetal‐cation‐centered groups PO4 expected from the existing models and theories. The SHG coefficients of LCPO are determined mainly by the occupied orbitals O 2p and Cs 5p as well as by the unoccupied orbitals Cs 5d and Li 2p. For the SHG response of a material, the polarizable atomic orbitals of the occupied and the unoccupied states are both important. Abstract : Metal centered : The cause for the large second‐harmonic generation (SHG) of LiCs2 PO4 is shown to be the metal‐cation‐centered CsO6 and LiO4 groups rather than the nonmetal‐cation‐centered PO4 groups.